Scholar publications and open access policies: the Ktisis case - Giannoulakis, Stamatios; Artemi, Petros; Kounoudes, Alexia Dini (My University, 2012)
Throughout the world, academic libraries have come to the conclusion that the development of institutional repositories must be one of their major goals. Institutional repositories are the means for libraries to provide access to the research product of the academic community and also to promote open access. The publication of the research results in open access journals assists in the global diffusion of this information. The open access movement is becoming very popular among the academic institutions. Today more than 320 organizations have signed the Berlin declaration on Open Access. The Library and Information Services at the Cyprus University of Technology is one of these organizations. By signing this declaration the University commits to promote and support Open Access encouraging the researchers to publish their work based on the Open Access policies. The Library has developed the first institutional repository in Cyprus, Ktisis. This paper briefly describes the implementation process of Ktisis and continues to examine the set of activities used in the strategic plan of Ktisis, including the definition of open access policies.
Keywords: Open access; Open source software